2020
DOI: 10.3389/fpsyg.2019.02812
|View full text |Cite|
|
Sign up to set email alerts
|

Is Cognitive Training Effective for Improving Executive Functions in Preschoolers? A Systematic Review and Meta-Analysis

Abstract: In the present meta-analysis, we examined the effect of cognitive training on the Executive Functions (EFs) of preschool children (age range: 3-6 years). We selected a final set of 32 studies from 27 papers with a total sample of 123 effect sizes. We found an overall effect of cognitive training for improving EF (g = 0.352; k = 123; p < 0.001), without significant difference between near and far transfer effects on executive domains. No significant additional outcome effects were found for behavioral-and learn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
86
1
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(125 citation statements)
references
References 80 publications
1
86
1
6
Order By: Relevance
“…Tasks that require rule switching are considered as flexible such as DCCS and gender-emotion switch tasks. We categorized go/no-go, flanker, and Stroop-like tasks as inhibition measurement tests because participants need to inhibit the distraction, pre-potent, and automatized response when performing the tasks (Scionti et al, 2020).…”
Section: Operational Definitionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tasks that require rule switching are considered as flexible such as DCCS and gender-emotion switch tasks. We categorized go/no-go, flanker, and Stroop-like tasks as inhibition measurement tests because participants need to inhibit the distraction, pre-potent, and automatized response when performing the tasks (Scionti et al, 2020).…”
Section: Operational Definitionsmentioning
confidence: 99%
“…The study also aimed to explore the transfer effects of computer-based training; therefore, we labeled the transfer effect of each effect size as near transfer or far transfer, based on the study by Scionti et al (2020). The effect sizes that measured the same aspect of EFs as interventions were defined as near-transfer, whereas those that measured the different aspects of EFs with the intervention were defined as far transfer.…”
Section: Operational Definitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several factors portend individual differences in EF including neurological differences (e.g., Short et al, 2019), early attention (e.g., Blankenship et al, 2019;Devine et al, 2019), and cognitive training (Scionti et al, 2020). Furthermore, several environmental factors including aspects of parenting (e.g., Hughes et al, 2013;Fay-Stammbach et al, 2014;Hughes and Devine, 2019), child care (e.g., Duncan et al, 2019), and stress (Blair, 2010) are associated with the development of young children's EF.…”
Section: Introductionmentioning
confidence: 99%
“…If lower-order cognitive training would be effective, we would therefore expect to find larger improvements following placebo training than following EF training or waitlist condition, which was not the case. A recent meta-analysis on EF training in very preterm children at preschool-age specifically (3-6 years of age) concluded that EF training does have positive results in this population, especially when it is non-computerized and in a group setting [83]. Therefore, we suggest that focus should be directed towards training programs that target younger children, combine exercise and tasks demanding EFs and take place in group settings.…”
Section: Discussionmentioning
confidence: 94%